Administración pública y su incidencia en la prestación de servicios al usuario - Velásquez Peñafiel, Sandra Jacquelin (2019)
The public administration comes to be constitute in everything that the state decides to do for the population is reflected from the social part to the economic, oriented to guide and promote strategies that improve the quality of life of citizens, reference is also made to the importance of public services in society since they allow us to provide social, family and personal well-being satisfying the needs of the user. They purpose of the research will basically be to create digital content to improve the functioning of the organization and the quality of the services it offers to the community, also disseminate information online to citizens about the services offered by the institution to achieve the goals set by the state, it should be mentioned that the main objective of the case study is focused on determining whether the public administration affects the provision of services to the user offered by the department of Crime Prevention Directorate of the Ministry of Interior, in this investigation, the survey was applied as a technique in order to obtain a quick and effective response to the problem posed within the organization, with the intention of improving the professional field to ensure sustainable development